Myth and Deity in Japan the interplay of Kami and Buddhas - Kamata, Toji 1951-; Sekimori, Gaynor (2017)
"Shinto is a tradition native to Japan that arose naturally on the eastern fringe of the Eurasian continent and was woven over many years into the fabric of people's everyday lives. When Buddhism entered the country in the sixth century, the two religions--rather than competing with or seeking to marginalize the other--coalesced, embracing many other folk deities as well to create a singular combinatory religious culture that continues to permeate Japan's cultural life today. This English translation of a book originally written in Japanese by one of the country's most knowledgeable, penetrating, and eclectic scholars of Japanese religion and spirituality presents an engaging overview of the country's religious legacy, as well as offering insights into how religion can become a force for peaceful coexistence, rather than violent extremism"--Back cover.
The mechanism of combination -- The encounter of Shinto and Buddhism in the early Japanese state -- The new Buddhism of the Heian period -- Kami and Buddhas in the medieval period -- Nativist studies and a new view of Kami-Buddha combination -- Epilogue : toward a new Kami-Buddha combination.
Translation of: Kami to hotoke no deau kuni (Kadokawa Corporation, 2009).
Includes bibliographical references and index.
Japan Foundation
Keywords: Shinto -- Relations -- Buddhism; Buddhism -- Relations -- Shinto; Japan -- Religion